2017
DOI: 10.1007/s40858-017-0194-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of parasitic nematodes in Kenyan rice fields and their relation to edaphic factors, rainfall and temperature

Abstract: Rice is the third most important crop in Kenya after maize and wheat. Plant parasitic nematodes (PPN) are a major rice production constraint. The objective of this study was to determine the distribution and abundance of rice PPN in Kenya and their association with environmental variables. Soil and plant samples were collected from rainfed upland and irrigated lowland rice fields in Kirogo, Thiba, Nyangati, Ombeyi, Kombura, Kakola and Mwambe Sub-locations. Twenty-two PPN genera were identified across all Sublo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
2
4
1
Order By: Relevance
“…Nematodes abundance and diversity are impacted by soil practices and soil texture. Our work supports previous findings that soil physicochemical factors and climatic variables are heavily linked to PPN communities composition and abundance levels (Palomares-Rius et al, 2015;Aït Hamza et al, 2018;Namu et al, 2018).…”
Section: Correspondences Of Plant Parasitic Nematodes To Climatic Varsupporting
confidence: 92%
See 2 more Smart Citations
“…Nematodes abundance and diversity are impacted by soil practices and soil texture. Our work supports previous findings that soil physicochemical factors and climatic variables are heavily linked to PPN communities composition and abundance levels (Palomares-Rius et al, 2015;Aït Hamza et al, 2018;Namu et al, 2018).…”
Section: Correspondences Of Plant Parasitic Nematodes To Climatic Varsupporting
confidence: 92%
“…The multiblock analysis showed that Ditylenchus, Helicotylenchus, Pratylenchus and Paratylenchus were related to the humidity that occurred in Taliouine while Aphelenchoides, Tylenchus, Tylenchorynchus and Dorylaimus were found in rainy locations of Taznakht. Herein, climatic conditions are the driving force to structure PPN communities particularly through rainfall and humidity (Aït Hamza et al, 2018;Ferreira et al, 2018;Namu et al, 2018). Conversely maximum temperature had an insignificant impact on PPN communities what has been confirmed by Namu et al (2018).…”
Section: Correspondences Of Plant Parasitic Nematodes To Climatic Varmentioning
confidence: 79%
See 1 more Smart Citation
“…In contrary to what has often been reported about the prevalence of rainfed rice nematode (Namu et al, 2018), only 2 genera (Helicotylenchus and Scutellonema) have been recorded from upland ecosystem in the study. The low nematode prevalence in the upland ecosystem as observed in this survey could be explained by the rice variety which is mainly cultivated in this area in Togo.…”
Section: Discussioncontrasting
confidence: 99%
“…were also not detected in the soils of Sagaing, indicating that rotation with paddy rice might be effective to control these PPN, due to the flooded conditions [21]. Indeed, Heterodera and some other PPN were not detected in paddy rice fields [22].…”
Section: Discussionmentioning
confidence: 95%